Risk factors for perinatal mortality in India: a systematic review of observational studies - Misra, Aroonima; Menon, Geetha; Sinha, Anju Pradhan; Singh, Shivani; Rao, M. Vishnu Vardhana; Sharma, Saurabh (International Journal Of Community Medicine And Public Health, 2022)
Perinatal mortality (PM) is a major public health problem in India and multiple maternal and foetal risk factors have been attributed to high perinatal mortality. This review aimed to systematically summarize the epidemiological literature on maternal and fetal risk factors for PM including those for still birth, intrauterine deaths; early neonatal mortality; early neonatal deaths in India. This systematic review was compliant with preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. We searched for peer-reviewed articles from three electronic bibliographic databases: MEDLINE, Embase, Google Scholar published between 1 January 2000 and 31 March 2019 that reported the risk factors of perinatal mortality in India. Observational studies (cross sectional, case-control and COHORT Studies). Eighteen articles were included in this review. The major risk factors identified for perinatal mortality in India were maternal age, parity, higher birth order and maternal anemia. Complications during pregnancy like ante partum hemorrhage, preeclampsia, obstructed labor, preterm labor and fetal factors like gestational age and low birth weight were documented as risk factors for perinatal deaths. Strengthening national health programs and targeted interventions for both antenatal and institutional care is required to bring down perinatal deaths in India.